A Grapevine Anthocyanin Acyltransferase, Transcriptionally Regulated by VvMYBA, Can Produce Most Acylated Anthocyanins Present in Grape Skins. Issue 3 (22nd September 2015) - Rinaldo, Amy R.; Cavallini, Erika; Jia, Yong; Moss, Sarah M.A.; McDavid, Debra A.J.; Hooper, Lauren C.; Robinson, Simon P.; Tornielli, Giovanni B.; Zenoni, Sara; Ford, Christopher M.; Boss, Paul K.; Walker, Amanda R.
Abstract : An anthocyanin acyltransferase with an unusual substrate flexibility is truncated in cv Pinot Noir, a grapevine cultivar lacking acylated red pigments. Abstract: Anthocyanins are flavonoid compounds responsible for red/purple colors in the leaves, fruit, and flowers of many plant species. They are produced through a multistep pathway that is controlled by MYB transcription factors. VvMYBA1 and VvMYBA2 activate anthocyanin biosynthesis in grapevine ( Vitis vinifera ) and are nonfunctional in white grapevine cultivars. In this study, transgenic grapevines with altered VvMYBA gene expression were developed, and transcript analysis was carried out on berries using a microarray technique. The results showed that VvMYBA is a positive regulator of the later stages of anthocyanin synthesis, modification, and transport in cv Shiraz. One up-regulated gene, ANTHOCYANIN 3-O-GLUCOSIDE-6″-O-ACYLTRANSFERASE ( Vv3AT ), encodes a BAHD acyltransferase protein (named after the first letter of the first four characterized proteins: BEAT [for acetyl CoA:benzylalcohol acetyltransferase], AHCT [for anthocyanin O- hydroxycinnamoyltransferase], HCBT [for anthranilate N- hydroxycinnamoyl/benzoyltransferase], and DAT [for deacetylvindoline 4- O- acetyltransferase]), belonging to a clade separate from most anthocyanin acyltransferases. Functional studies (in planta and in vitro) show that Vv3AT has a broad anthocyanin substrate specificity and can also utilize both aliphatic and aromatic acyl donors, a novel activity for this enzyme family found in nature. In cv Pinot Noir, a red-berried grapevine mutant lacking acylated anthocyanins, Vv3AT contains a nonsense mutation encoding a truncated protein that lacks two motifs required for BAHD protein activity. Promoter activation assays confirm that Vv3AT transcription is activated by VvMYBA1, which adds to the current understanding of the regulation of the BAHD gene family. The flexibility of Vv3AT to use both classes of acyl donors will be useful in the engineering of anthocyanins in planta or in vitro.